(untitled) (Journal of the College of Basic Education, 2022)
Evaluation is a systematic method aimed at determining the extent to which a particular program achieves the specific educational goals that have been previously identified and obtaining evidence to justify how to improve this program in the future. The school curricula (books) are the main effective tool in achieving the objectives of education and society, whether it is developed or developing. They differ according to the philosophy embraced by each society, and this philosophy is a source of trends and values ​​that govern patterns of behavior and direct its activity. Therefore, many countries that aspire through their curricula (books) to reach the forefront of developed countries, therefore, resort to continuous review of the development of these books to meet the requirements of society. in construction and growth.